1993
DOI: 10.1121/1.406052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extended training on /r/ and /l/ identification by native speakers of Japanese

Abstract: It has been reported (1) that being exposed to the American English (AE) speaking environment in adulthood has less of an effect on the perception of AE /r/ and /l/ sounds for native speakers of Japanese than experience at younger ages, and (2) that laboratory training of those sounds on adult-Japanese has little effect. Recently, however, Logan et al. [J. S. Logan et al., J. Acoust. Soc. Am. 89, 874–886 (1991)] and Lively et al. [J. Acoust. Soc. Am. (1993)] showed that identification training with natural tok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…For example, highly successful learning of the English /r/-/l/ contrast by Japanese listeners has been demonstrated following training with words that placed /r/ and /l/ in various phonetic environments as produced by various native talkers of English. This learning has been shown to generalize to untrained words and to novel talkers, to transfer to improved production of the contrast and to be retained for at least 6 months following initial training (Logan et al, 1991;Lively et al, 1993Lively et al, , 1994Yamada, 1993;Bradlow et al, 1997Bradlow et al, , 1999. Similarly successful learning has been demonstrated for other non-native contrasts following similar high-variability training procedures including training of English listeners on Chinese lexical tone contrasts (Wang, Spence, Jongman and Sereno, 1999;Wang, Jongman and Sereno, 2003), training of English and Japanese listeners on Hindi dental and retroflex stops (Pruitt, 1995), training English listeners on Japanese vowel length contrasts (Yamada, Yamada and Strange, 1996), training Chinese listeners on English word-final /t/ and /d/ (Flege, 1995), and training English listeners on various German vowel contrasts (Kingston, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, highly successful learning of the English /r/-/l/ contrast by Japanese listeners has been demonstrated following training with words that placed /r/ and /l/ in various phonetic environments as produced by various native talkers of English. This learning has been shown to generalize to untrained words and to novel talkers, to transfer to improved production of the contrast and to be retained for at least 6 months following initial training (Logan et al, 1991;Lively et al, 1993Lively et al, , 1994Yamada, 1993;Bradlow et al, 1997Bradlow et al, , 1999. Similarly successful learning has been demonstrated for other non-native contrasts following similar high-variability training procedures including training of English listeners on Chinese lexical tone contrasts (Wang, Spence, Jongman and Sereno, 1999;Wang, Jongman and Sereno, 2003), training of English and Japanese listeners on Hindi dental and retroflex stops (Pruitt, 1995), training English listeners on Japanese vowel length contrasts (Yamada, Yamada and Strange, 1996), training Chinese listeners on English word-final /t/ and /d/ (Flege, 1995), and training English listeners on various German vowel contrasts (Kingston, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The stimuli and procedure used to train these subjects have been described in detail in our earlier papers (see Bradlow et aI., 1997;Lively et aI., 1993;Lively et aI., 1994;Logan et aI., 1991;Yamada, 1993). In the present report, therefore, we will provide only a brief description of our training methodology, and we refer the reader to the previous papers for additional details.…”
Section: Perception Trainingmentioning
confidence: 99%
“…Furthermore, the trainees were presented with naturally produced tokens demands of the identification task used to assess changes in spoken word recognition performance before and after training. The results of several initial training studies using this "high-variability" perceptual training procedure demonstrated that Japanese trainees could acquire robust Irl and III phonetic categories, which they could apply more generally in understanding novel talkers and novel tokens (Lively, Logan, & Pisoni, 1993;Logan et al, 1991;Yamada, 1993). Moreover, these changes were retained for several months after the completion of training (see Lively, Pisoni, Yamada, Tohkura, & Yamada, 1994).…”
mentioning
confidence: 99%
“…(All informants were students of English at university and had taken a pronunciation class in English, as described in Section II.) Although in most studies reporting on the positive effect of both perception and production training on learners' pronunciation the testing part follows immediately or only a short time after the training session and the informants are trained on one particular pronunciation feature only (on the effect of training the English /r/-/l/ contrast to L1 Japanese speakers, see, for example, Yamada, 1993;Bradlow et al, 1997), it is likely that a semester-long pronunciation class in the year preceding the recordings, in which aspiration was one of the features dealt with, still had an important effect on the learners' pronunciation.…”
Section: Acquiring a New L2 Contrast: The Role Of Acoustic Salience mentioning
confidence: 99%